Somalia : First Review Under the Extended Credit Facility-Press Release; Staff Report; and Statement by the Executive Director for Somalia. (IMF Staff Country Reports; Country Report ;, 2020)
Soon after reaching the HIPC Decision Point and embarking on a new IMFsupported program aimed at supporting the implementation of the authorities' National Development Plan and lifting growth, Somalia was hit by a triple shock of flooding, desert locusts, and, importantly, the coronavirus pandemic. Prompt action by the authorities and support from the international community has helped mitigate the impact on peoples' lives and livelihoods, however, these shocks have had a significant impact on economic activity, exports, and domestic fiscal revenues.